Evaluation of mechanical and wear properties of AA6063/(Si3N4)6%–12% /(CuN2O6)2%–4% composite via PM route and optimization through robust design technique. (1st July 2022) - Sureshkumar, P; Sasikumar, C; Rajan, S Thanga Kasi; Jagadeesha, T; L, Natrayan; Ravichandran, M; Veeman, Dhinakaran; Borek, Wojciech
Abstract: The study is to investigate the physical, mechanical, and tribological properties of Al6063 alloy reinforced by Silicon Nitride (Si3 N4 ) & compound Copper Nitrate (CuN2 O6 ) processed via Powder Metallurgy (PM) Techniques. Incorporation of reinforcement in matrix material ranged from 6 to 12% Si3 N4 in a 6-step interval, and 2 to 6%CuN2 O6 in a two-step interval. The characterizations were made on the PM produced specimens using OM, EDS, XRD and hardness. The reinforcement particles were distributed uniformly is attributed by homogeneous mixer of matrix and reinforcements. The tests were carried out in accordance with ASTM Standards on the Al6063 alloy and its composites. The test findings show that as the reinforcing percentage of ceramic and inorganic compound is increased, properties such as hardness and density rise monolithically and considerably. The dispersion of Si3 N4 and CuN2 O6 reinforcement in the AA6061 matrix was ensured by x-ray diffraction patterns. In comparison to the base alloy, the hardness of AA6063/12%Si3 N4 /6% CuN2 O6 improved by 88% due to the mismatch of thermal expansion between the Al matrix and reinforcement causes huge internal stress, causing the aluminium matrix to deform plastically to lodge the smaller volume expansion of Si3 N4 and CuN2 O6 particles. The dry sliding wear test was carried out on a tribometer with a pin-on-disc arrangement, and the findings show that the composite has a higher wear resistance. The Taguchi design of experiments was used to investigate the solution containing parameters employing an orthogonal array, the signal-to-noise ratio, and analysis of variance. The weight percentage of Si3 N4 /CuN2 O6 compound and the relationship between wt% of reinforcement and applied load had the highest impact on composite wear resistance, accounted for 31.66%. Before and after the wear morphology during the wear test, images from a scanning electron microscope and energy dispersive microscopy were used to examine the manufactured composites.